2016
DOI: 10.1016/j.anifeedsci.2016.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feed form and energy concentration of the rearing phase diets on productivity, digestive tract development and body measurements of brown-egg laying hens fed diets varying in energy concentration from 17 to 46 wk of age

Abstract: a b s t r a c tThe influence of feed form and energy content of the rearing phase diets on hen productivity, gastrointestinal tract (GIT) traits and body measurements was studied in brown-egg laying hens fed diets differing in energy concentration from 17 to 46 wk of age. The experiment was completely randomized with 12 treatments arranged as a (2 × 3) × 2 factorial with two feed forms (mash vs. crumbles) and three AME n concentrations of the rearing phase diets (low, medium and high) and two AME n concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
5
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 40 publications
11
5
1
2
Order By: Relevance
“…The data presented herein indicate that the potential beneficial effects of DF on the size and development of the GIT are not long lasting and disappear once the birds are fed a common commercial layer diet . In this respect, Saldaña et al (2016) reported similar size and development of the different organs of the GIT in 46 wk-old hens that were fed mash or crumble diets during the rearing phase, consistent with the results reported herein. Also, Saldaña et al (2015a) reported that the effects of feed form on the GIT traits of pullets from 0 to 17 wk of age, reverted quickly when the birds were changed from receiving crumbles to receiving mash diets.…”
Section: Digestive Tract Traits and Body Measurementssupporting
confidence: 81%
See 4 more Smart Citations
“…The data presented herein indicate that the potential beneficial effects of DF on the size and development of the GIT are not long lasting and disappear once the birds are fed a common commercial layer diet . In this respect, Saldaña et al (2016) reported similar size and development of the different organs of the GIT in 46 wk-old hens that were fed mash or crumble diets during the rearing phase, consistent with the results reported herein. Also, Saldaña et al (2015a) reported that the effects of feed form on the GIT traits of pullets from 0 to 17 wk of age, reverted quickly when the birds were changed from receiving crumbles to receiving mash diets.…”
Section: Digestive Tract Traits and Body Measurementssupporting
confidence: 81%
“…From 17 to 46 wk of age, egg production was high in all hens, irrespective of the energy concentration of the diet, in agreement with data of Grobas et al (1999a,b) comparing diets with 2,680 and 2,810 kcal AMEn/kg and Saldaña et al (2016) comparing diets with 2,650 and 2,750 kcal/kg in brown egg-laying hens. Similar data have been reported by Jalal et al (2006) and Murugesan and Persia (2013) in Single Comb White Leghorn hens fed diets containing 2,800 to 2,900 kcal AMEn/kg.…”
Section: Hen Productivity and Egg Qualitysupporting
confidence: 81%
See 3 more Smart Citations